DMAP-Catalyzed Reaction of Diethyl 1,3-Acetonedicarboxylate with 2-Hydroxybenzylideneindenediones: Facile Synthesis of Fluorenone-Fused Coumarins - Shkoor, Mohanad; Bayari, Raghad (Synlett, 2021)
The base-catalyzed reaction of diethyl 1,3-acetonedicarboxylate with 2-hydroxybenzylidene indenediones was studied. The reaction provides a facile and expeditious protocol for the synthesis of natural product inspired fluorenone-fused coumarins in good to very good yields. This process resembles a combination of domino Michael–intramolecular Knoevenagel–aromatization–lactonization reactions in a single step. Although this reaction operates with many bases, the best yields were obtained with DMAP as a catalyst. This protocol could open new potential avenues for the synthesis of fused coumarins by the reaction of substituted β-keto esters with different 2-(2-hydroxybenzylidenes) of 1,3-dicarbonyl compounds.
Keywords: coumarin; fluorenone; indandione; DMAP; benzo[c]chromen-6-ones